O Impacto da política monetária sobre os juros e crédito bancário - Harbache, Rafaela (2009)
In the last years, credit market has shown strong growth since interest rates and bank spreads have followed a declined route. This dissertation analyzes the impact of the monetary policy on the bank margins and interest rates of some type of credit operations and tests the relation between interest rates, loans and GDP. The cointegration test results can not reject the hypothesis that Selic rate could be affecting the bank margins and interest rates and also that there is a long term relation between interest rates, loans and GDP.